2010
DOI: 10.1373/clinchem.2009.142364
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein Adversely Alters the Protein–Protein Interaction of the Endothelial Isoform of Nitric Oxide Synthase

Abstract: BACKGROUND: C-reactive protein (CRP) inhibits the activity of the endothelial isoform of nitric oxide synthase (eNOS) via uncoupling of the enzyme both in vitro and in vivo. eNOS activity appears to be related in part to its interaction with other cellular proteins, including heat shock protein 90 (Hsp90), caveolin-1, and porin. In this study, we examined the effect of CRP treatment of human aortic endothelial cells (HAECs) on eNOS interaction with caveolin-1, Hsp90, and porin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Earlier observations demonstrated that CRP levels correlated inversely with endothelial vasoreactivity. The most compelling data implicating CRP as a determinant of endothelial dysfunction were studies demonstrating that human CRP reduced basal and stimulated nitric oxide release from arterial and venous endothelial cells [9, 10]. In human aortic endothelial cells (HAEC), CRP resulted in significant reduction in mRNA and protein for endothelial nitric oxide synthase (eNOS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier observations demonstrated that CRP levels correlated inversely with endothelial vasoreactivity. The most compelling data implicating CRP as a determinant of endothelial dysfunction were studies demonstrating that human CRP reduced basal and stimulated nitric oxide release from arterial and venous endothelial cells [9, 10]. In human aortic endothelial cells (HAEC), CRP resulted in significant reduction in mRNA and protein for endothelial nitric oxide synthase (eNOS).…”
Section: Introductionmentioning
confidence: 99%
“…In human aortic endothelial cells (HAEC), CRP resulted in significant reduction in mRNA and protein for endothelial nitric oxide synthase (eNOS). Furthermore, CRP reduced eNOS activity (ie, conversion of L-arginine to L-citrulline) and bioactivity (secretion of cyclic guanosine 5′-monophosphate [cGMP]), in part through decreasing eNOS mRNA stability [9, 10]. CRP mediates uncoupling of eNOS via stimulation of NADPH oxidase and inhibition of GTP cyclohydrolase [11].…”
Section: Introductionmentioning
confidence: 99%
“…3-Hydroxy-3-methylglutaryl-CoA reductase inhibitors can improve the impaired endothelial dysfunction of the aorta in spontaneously hypertensive rats and may activate eNOS by phosphorylation and a decrease of Cav-1 abundance (131). In contrast, a 24-h treatment of C-reactive protein increased eNOS binding to Cav-1 in human aortic endothelial cells, thereby negatively regulating eNOS (141). Methyl-␤-cyclodextrin can inhibit caveolae-mediated endocytosis by moving cholesterol out of lysosomes and prevent eNOS-dependent NO production at the same time (80).…”
Section: Caveolins and Coexpression Partnersmentioning
confidence: 96%
“…Hsp90 promotes these phosphorylation events by potentially increasing the binding affinity for eNOS and Akt and causing a conformational shift that unmasks sites for modification [60, 61]. Several eNOS agonists stimulate rapid eNOS-hsp90 interaction and blockade of this partnership limits NO production and vasorelaxation [55, 62] with pathological conditions leading to a decrease in the association of these two proteins [63, 64]. …”
Section: Regulation Of No Production: the Dynamic Modulation Of Enosmentioning
confidence: 99%